ON POSITIVE EIGENVALUES OF THE DISCRETE SCHRÖDINGER OPERATOR WITH A NON-LOCAL POTENTIAL - Lakaev, Shukhrat (Scientific practical conference, 2026)
On the dimensional lattice the discrete Schrödinger operator with a non-local potential constructed via the Dirac delta function and shift operator considered. The dependence of positive eigenvalues existence of the operator on the parameters is explicitly derived.